YouTube and Bilibili as sources of information on oral cancer: cross-sectional content analysis study - Qilei zhang; Zhe Li; Huiping Zhang; Ling Han; Shugang Zhao; Siyu Jia (Scientific Reports)
Abstract This study aims to evaluate the informational quality of oral cancer-related videos on YouTube and Bilibili. A total of 300 oral videos that met the inclusion and exclusion criteria were selected for analysis. The selection comprised 150 videos from 111 uploaders on YouTube and 150 videos from 134 uploaders on Bilibili. YouTube videos received a greater number of views and likes, while there was no significant difference in average likes per 30 days or comments between the two platforms. The majority of YouTube uploaders were hospitals/non-profit organizations (66.7%) and for-profit companies (17.1%), while Bilibili uploaders were mainly self-media (55.2%) and doctors (29.1%). YouTube videos covered a broader range of topics compared to Bilibili videos. Though solo narration was the most prevalent video style across both platforms, YouTube exhibited a higher preference for TV shows/documentaries (31.3%). Video quality was assessed using the four tools: Though mDISCERN (modified DISCERN) and PEMAT-Actionability (Patient Education Materials Assessment Tool) were similar across platforms, YouTube videos scored higher on PEMAT-Understandability, VIQI (Video Information and Quality Index), and GQS (Global Quality Score) in comparison to Bilibili videos. Videos produced by health professionals were considered more reliable. Spearman correlation analysis revealed no strong relationships between video quality and audience interaction. In conclusion, YouTube videos exhibited higher audience engagement and video quality, yet improvements are needed on both platforms. In order to promote high-quality health information, it is essential to encourage the development of more professional content creators and to optimize platform algorithms.